1982
DOI: 10.1159/000176581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin B<sub>6</sub> and B<sub>1</sub> Deficiencies on the Intestinal Uptake of Calcium, Zinc and Cadmium

Abstract: A chronic vitamin B6 deficiency in rats resulted in a non-specific increase (44–51 %) in the in vitro intestinal uptake of both essential (Ca and Zn) and non-essential toxic metal (Cd) ions, whereas an acute B6-deficient state only affected the Zn uptake rate. In vitamin B1 -deficient animals, a specific decrease (30–32%) was observed in Ca and Zn uptake with a 59% increase in the intestinal uptake of Cd. These altered metal ion uptake rates were probably not a result of hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Prasad et al [27] reported increased intestinal uptake of calcium in vitamin B6 deficiency, possibly due to a change in the brush border, allowing more absorption. Another cause of nephrolithiasis in pyridoxine deficiency is increased intestinal absorption of both endogenous and exogenous oxalate [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Prasad et al [27] reported increased intestinal uptake of calcium in vitamin B6 deficiency, possibly due to a change in the brush border, allowing more absorption. Another cause of nephrolithiasis in pyridoxine deficiency is increased intestinal absorption of both endogenous and exogenous oxalate [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…These minerals also act as cofactors of antioxidant enzymes; therefore, they can reduce the cadmium-induced oxidative stress via antioxidant enzymatic activity (Koekkoek and van Zanten, 2016). Studies have shown that a deficiency of vitamin B1 and B6 increased susceptibility to cadmium toxicity (Prasad et al, 1982). Hence, supplementation with these vitamins is a suggested method for providing protection against cadmium-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%